Narrative theology: An adequate paradigm for theological reflection? - Van Huyssteen, J. Wentzel (Hervormde teologiese studies, 1989)
As reflection on the religious claims embedded in stories, narrative theology touches the nerve of theology: what is the epistemological status of theological theories if they are based on discourse which is fundamentally narrative and metaphorical? This paper analyzes this question, along with the important differences between ‘pure’ and ‘impure’ narrative theology. Crucial problems arise from this and are discussed: the epistemological problem of determining criteria for assessing the truth claims of theological statements; and the hermeneutical criteria for distinguishing between good and bad receptions of Christianity’s classic text.